1995
DOI: 10.1073/pnas.92.7.2539
|View full text |Cite
|
Sign up to set email alerts
|

Aceruloplasminemia: molecular characterization of this disorder of iron metabolism.

Abstract: Ceruloplasmin is an abundant alpha 2-serum glycoprotein that contains 95% of the copper found in the plasma of vertebrate species. We report here on the identification of a genetic defect in the ceruloplasmin gene in a patient previously noted to have a total absence of circulating serum ceruloplasmin in association with late-onset retinal and basal ganglia degeneration. In this patient T2 (transverse relaxation time)-weighted magnetic resonance imaging of the brain revealed basal ganglia densities consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
274
0
9

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(292 citation statements)
references
References 31 publications
8
274
0
9
Order By: Relevance
“…In the blood, copper is bound to ceruloplasmin, albumin, possibly transcuprein, and small molecules, such as histidine. Although the majority of copper is bound to ceruloplasmin and albumin, neither of these two proteins seems to be necessary for normal copper absorption or transport because aceruloplasminia patients (who lack ceruloplasmin) and analbuminemic rats (with albumin deficiency) both have normal copper metabolism (14)(15)(16)34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the blood, copper is bound to ceruloplasmin, albumin, possibly transcuprein, and small molecules, such as histidine. Although the majority of copper is bound to ceruloplasmin and albumin, neither of these two proteins seems to be necessary for normal copper absorption or transport because aceruloplasminia patients (who lack ceruloplasmin) and analbuminemic rats (with albumin deficiency) both have normal copper metabolism (14)(15)(16)34).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that one avenue for uptake is through ceruloplasmin, the most abundant copper-containing protein in the circulation, which might deliver copper to multiple tissues through a ceruloplasmin receptor (10)(11)(12)(13). Later studies on aceruloplasminemic patients indicated that these patients have defects in iron homeostasis, whereas copper metabolism is normal (14)(15)(16). This indicates that ceruloplasmin is at least not necessary for normal copper transport.…”
mentioning
confidence: 99%
“…Ceruloplasmin is another major copper-binding protein, which functions as a ferroxidase to promote iron export [168,169]. The protein requires copper binding to perform this function, and low copper levels could lead to iron accumulation by impairing ceruloplasminmediated iron export [170].…”
Section: Coppermentioning
confidence: 99%
“…This notion is witnessed by an increased brain iron content in aceruloplasminemia and neuroferritinopathy which are hereditary disorders caused by dysfunction of proteins involved in the transport and storage of iron, namely in ceruloplasmin [12] and ferritin light chain (FTL) [13]. Iron is essential for many cellular functions, including energy production, DNA synthesis and repair, phospholipid metabolism, myelination and neurotransmitter synthesis [5].…”
Section: Causes and Consequences Of Cerebral Iron Accumulationmentioning
confidence: 99%
“…Aceruloplasminemia is caused by a mutation in the gene coding for ceruloplasmin protein [12]. Systemic iron accumulation is a consequence of the lack of ceruloplasmin ferroxidase activity preventing the cellular iron efflux.…”
Section: Aceruloplasminemiamentioning
confidence: 99%